(untitled) (Journal of Philosophy Culture and Political Science, 2018)
There formed religious diversity in Kazakhstan, which includes both traditional for Kazakhstan creeds, and new, previously not existing in Kazakhstan religious movements and organizations. This process according to the general opinion of the researchers began in 1990 when the religious lifting was supported by the authorities, who saw in religion one of the means to fill the ideological vacuum. By 2000, the number of religious movements in Kazakhstan increased to four and a half thousand. This situation is a threat to the national security of the state and the government took measures for their prevention. Especially many citizens are disturbed by policy propaganda of the Gospel among non-Christian population. There were a lot of publications in mass media. Kazakhstan dilemma, with one hand declared the policy of democracy and religious tolerance, as with other safety and security of citizens. In 2011 a new law ‘On religious activities and religious associations’ was taken. On results of work of re-registration of religious associations, the number of neo-Protestant associations, who were engaged in evangelization, decreased in 1,5-2 times. One of these active organisations ‘Seventh Day Adventists’ before the re-registration, there were 67, now there are 42 local religious associations. How to explain this situation? Why the state shows an example of democracy and the guarantee of the freedom of religion and all kinds of missionary activity was forced to take such steps in relation to religious organizations? The answer is simple: it is a way to protect citizens from the work of pseudo-religious movements and national security. The article was Seventh Day Adventists preaches ideas contrary to the traditional worldview of Christianity. The authors argue that the emergence and spread the teachings of Adventists and teachings of all the new trends of the XIX-XX centuries are identical: leaders announce their prophetic visions of history and endless doctrinal disputes on issues of faith. Keywords: Gospel, community, prophecies, end of the world, the local Church, the local conference, Union conference.